A Simple Braking Method for Six-phase Induction Motor Drives with Unidirectional Power Flow in the Base-Speed Region: Enhancing the Braking Capability of Six-phase Induction Motor Drives with Control Scheme Reconfiguration (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Induction motor drives supplied from diode front-end rectifiers are commonly used in industrial applications due to their low cost and reliability. However, the two-quadrant operation of such a topology makes the regenerative braking impossible. Braking resistors can be used to dissipate the braking power and provide enhanced braking capability, but additional hardware is then necessary. Alternatively, the braking power can be dissipated within the invertermotor by control software reconfiguration. In this scenario, the additional degrees of freedom of multiphase drives can be used to increase the system losses without disturbing the flux and torque production. Experimental results confirm the possibility to enhance the braking capability of six-phase drives with only few changes in the control scheme.